Clinical Efficacy Analysis of Conbercept Intravitreal Injection for Fundus Diseases Based on Computer Simulation. Issue 3 (February 2021) - Ren, Cong; Li, Zhongen; Jiang, Wenjun; Wang, Xingrong; Bi, Hongsheng; Guo, Bin
Abstract: Fundus diseases can seriously damage the visual acuity of patients, including age-related macular degeneration (ARMD), retinal choroidal neovascularization (CNV), retinal vein occlusion (RVO), central serous chorioretinopathy (CSC), diabetic retinopathy (DR), etc. At the same time, fundus disease generally has a long course, high severity, long-term delay, high recurrence rate, and as long as the patients do not receive timely treatment or do not receive the correct treatment, there will be a variety of complications, causing serious damage to the structure of the patient's eyes and the patient's visual function. Clinical trial simulation (CTS) is a newly emerging interdisciplinary subject in recent years. With the increasing cost in the process of new drug development, computer simulation technology has attracted extensive attention of pharmaceutical enterprises. Clinical treatment of fundus diseases includes hormone therapy, etiological treatment, vitrectomy, laser treatment, etc, But the effect is different. This study mainly analyzes the effect of intravitreal injection of conbercept in the treatment of fundus diseases. Based on the analysis and research of CTS research at home and abroad, aiming at the relationship between dosage, blood concentration and efficacy, the change of blood concentration under different dosage was analyzed, and the influence on drug effect under different administration scheme was predicted. Main work: establishment of simulation model (including proportional advantage model, pharmacokinetics / pharmacodynamics model), simulation calculation, model simulation and result analysis.